Preferences for support in managing symptoms of an asthma flare-up: a pilot study of a discrete choice experiment. (1st February 2023) - O'Connell, Selena; Queally, Michelle; Savage, Eileen; Murphy, Desmond M.; Mc Carthy, Vera J. C.
Abstract: Objective: Information on the preferences of people with asthma for support in managing a flare-up can inform service design which may facilitate appropriate help-seeking. To date, little is known about support preferences for managing a flare-up. The aim of this study was to develop and pilot a discrete choice experiment (DCE) to elicit the preferences of people with asthma with regards to support in managing a flare-up. Methods: Steps in developing the DCE included identification and selection of attributes and levels of the support services, construction of choice tasks, experimental design, construction of DCE instrument, and pretest (n=16) and pilot (n=38) studies of the DCE instrument. A multinomial logit model was used to examine the strength and direction of the six attributes in the pilot study. Results: Our results indicate that from a patient perspective, having a healthcare professional that listens to their concerns was the most valued attribute of support in asthma flare-up management. The other features of support valued by participants were timely access to consultation, a healthcare professional with knowledge of their patient history, a specialist doctor and face-to-face communication. Having a written action plan was the least valued attribute. Conclusions: Our findings suggest patient preference for a model of support in managing their symptoms which includes timely, face-to-face access to a healthcare professional that knows them and listens to their concerns. The findings of the pilot study need to be verified with a larger sample and using models to account for preference heterogeneity.